آليات الانتقال إلى اقتصاد المعرفة: قراءة في مؤشر المعرفة العربي لسنة 2016 -حالة الجزائر - بوقموم, محمد; كنيدة, زليخـة (Recherches économiques et managériales, 2018)
مما لا شك فيه أن الانتقال إلى اقتصاد المعرفة، يتطلب وجود بيئة معرفية ، تقوم على أربعة ركائز أساسية تشكل مقومات الاندماج في هذا الاقتصاد وهي : البنية التحتية ل تكنولوجيا المعلومات والاتص الات؛ الحوافز الاقتصادية والنظام المؤسسي؛ الاهتمام بعمليات التعليم والتدريب وخاصة التعليم النوعي؛ دعم عمليات الإبداع والابتكار . تحاول هذه الدراسـة تسليط الضوء على آليات انتقال الجزائر إلى اقتصاد المعرفة، ومدى توافر المؤشرات الرئيسة للاندماج فيه، وفقا لمنهجية مؤشر المعرفة العربي لسنة 201 6 . الكلمات المفتاحية : اقتصاد المعرفة، مؤشر اقتصاد المعرفة العربي 2016 ، مؤشرات اقتصاد المعرفة في الجزائر . Abstract   The transition to a knowledge economy requires a knowledge environment based on four basic pillars that are an integral part of this economy: information and communication technology infrastructure; economic incentives and the institutional system; attention to education and training processes, particularly qualitative education; support Creative processes and innovation . This study would spotlight on the mechanisms of Algeria's transition to the knowledge economy and the extent to which it has key indicators available for integration, in accordance with the Arabic Knowledge Index 2016 methodology. Keywords : Knowledge Economy , Arab Knowledge Economy Index 2016, indicators of the knowledge economy in Algeria .